2014
DOI: 10.5194/amt-7-2829-2014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature calibration on the OC–EC results from a dual-optics thermal carbon analyzer

Abstract: Abstract. Thermal–optical analysis (TOA) is a widely used technique that fractionates carbonaceous aerosol particles into organic and elemental carbon (OC and EC), or carbonate. Thermal sub-fractions of evolved OC and EC are also used for source identification and apportionment; thus, oven temperature accuracy during TOA analysis is essential. Evidence now indicates that the "actual" sample (filter) temperature and the temperature measured by the built-in oven thermocouple (or set-point temperature) can differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Among other factors, speciation depends on the sample composition, particle morphology, atmosphere surrounding the sample, sample substrate and matrix, thermal program, instrument design (including char correction method, if used), and nature of the thermal decomposition process (pyrolysis/combustion/volatilization). Thermal techniques used for OC-EC speciation in airborne particulate matter have mainly included thermal-optical transmittance (TOT; Birch and Cary 1996; Birch 1998; Peterson and Richards 2002; Chow et al 2005; Bauer et al 2009; Pavlovic et al 2014), thermal/optical reflectance (TOR; Han et al 2007; Chow et al 2007; Pavlovic et al 2014), thermogravimetric analysis (TGA; Iwatsuki et al 1998; Stratakis and Stamatelos 2003; Lapuerta et al 2007); and thermal manganese dioxide oxidation (TOM; Fung 1990; Park et al 2005). Current methods are mainly based on NIOSH Method 5040 and similar protocols, which use a Sunset Laboratory analyzer, or the IMPROVE protocol, based on a different analyzer design (Desert Research Institute [DRI], Reno, NV).…”
Section: Resultsmentioning
confidence: 99%
“…Among other factors, speciation depends on the sample composition, particle morphology, atmosphere surrounding the sample, sample substrate and matrix, thermal program, instrument design (including char correction method, if used), and nature of the thermal decomposition process (pyrolysis/combustion/volatilization). Thermal techniques used for OC-EC speciation in airborne particulate matter have mainly included thermal-optical transmittance (TOT; Birch and Cary 1996; Birch 1998; Peterson and Richards 2002; Chow et al 2005; Bauer et al 2009; Pavlovic et al 2014), thermal/optical reflectance (TOR; Han et al 2007; Chow et al 2007; Pavlovic et al 2014), thermogravimetric analysis (TGA; Iwatsuki et al 1998; Stratakis and Stamatelos 2003; Lapuerta et al 2007); and thermal manganese dioxide oxidation (TOM; Fung 1990; Park et al 2005). Current methods are mainly based on NIOSH Method 5040 and similar protocols, which use a Sunset Laboratory analyzer, or the IMPROVE protocol, based on a different analyzer design (Desert Research Institute [DRI], Reno, NV).…”
Section: Resultsmentioning
confidence: 99%
“…However, temperature variability within the oven may result in different temperatures at the sample and the sensor (Phuah et al, 2009). Sample temperatures have been found to differ from sensor temperatures by 10 to 85 • C in both the DRI and Sunset analyzers by IMPROVE_A, NIOSH-like and EUSAAR_2 protocols (Chow et al, 2005b;Phuah et al, 2009;Pavlovic et al, 2014;Panteliadis et al, 2015). Chow et al (2005b) demonstrated that temperature biases of 14 to 22…”
Section: Thermal-optical Analysis Protocolsmentioning
confidence: 99%
“…The R was calculated from relatively big sample size (between 73 and 93 samples analyzed) which means that uncertainty in true value of the correlation is small and equal to zero for R > 0.25. The semivolatile PM mass in this study is defined as the fraction of total organic carbon (OC) measured by the NIOSH 5040 temperature protocol that evolves at temperatures lower than 310 °C and is called the OC1 subfraction . The semivolatile PN fraction is linked to typical diesel nucleation mode particles with mobility diameter Dp < 50nm and is referred to here as PN 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Online, real time instrumentation was used to monitor gaseous emissions from the exhaust duct as described in Yelverton et al These measurements included carbon monoxide (CO), carbon dioxide (CO 2 ), oxygen (O 2 ), and nitrogen oxides (NO x ). Particulate matter measurements were performed after dilution and included: black carbon (BC), aerosol light absorption and scattering, particle size distribution, filter collection for total PM mass, and thermal optical analyses for organic (OC) and elemental (EC) carbon by NIOSH 5040 thermal optical protocol. , The OC values presented here are not blank-corrected for the amount of OC present in the dilution air. Therefore, OC concentrations presented display trends and not necessarily the absolute values in the exhaust.…”
Section: Methodsmentioning
confidence: 99%